Karideslerde 4-hexylresorcinol kalıntılarının belirlenmesi için hızlı bir HPLC Metodu - (:unkn) unknown (My University, 2014)
Bu makalede, karidesten 4-hexylresorcinol'un ekstraksiyonu, yüksek basınçlı sıvı kromotografisinde (HPLC) ayırımı ve miktarının belirlenmesi ile ilgili hızlı bir metot anlatılmıştır. Bu modifiye metot, kısa ön hazırlık ve HPLC' de keskin pik ayırımı ile daha önceki metotlara gore daha hızlıdır (örnek hazırlığı, ekstraksiyon, ayırım ve miktarın belirlenmesi toplamda 40 dakika). İki eğride de korelasyon katsayısı (r2) 0,999 un üzerinde ölçülmüştür. 1.5-2.5 mg/kg lık geri kazanım çalışma aralığının güvenilirlik değeri yaklaşık % 95 bulunmuştur. Tespit limiti ve ölçüm limiti 0.04 ve 0.06 mg/kg olarak bulunmuştur.

A rapid method for the extraction, separation and quantification of the 4-hexylresorcinol from shrimp with high performance liquid chromatography (HPLC) is described. This modified method is faster than previously described methods with short pre–preparation and sharp resolution in HPLC procedures (sample preparation, extraction, separation and quantification total 40 min.). The coefficients of determinations (r2 ) measured for 4-hexylresorcinol were obtained over 0,999 in each curve. The confidence interval of the recovery working range of 1.5–2.5 mg/kg was approximately 95%. Limits of detection and quantitation were determined as 0.04 and 0.06 mg/kg for shrimp.
A RAPID HPLC METHOD FOR DETERMINATION OF 4-HEXYLRESORCINOL RESIDUES IN SHRIMP
Keywords: Kimya, Analitik